Iot air exchange control system - Sultanbay, A. J. (Харківський національний автомобільно-дорожній універститет, 2024)
The article is devoted to the research and development of an intelligently controlled air exchange system based on IoT technologies for use in urban environments. With increasing urbanization and environmental degradation, traditional ventilation systems cannot cope with changing conditions that require the development of new air quality management solutions. This study proposes a system that uses air quality sensors to monitor pollution, temperature and humidity in real time, as well as IoT technology to automatically adjust air flow. During the research, the system was modeled and experimental tests were carried out. The results showed that the introduction of an intelligent system will significantly improve indoor air quality by reducing pollution levels by 15-25% compared with traditional air exchange methods. The system also helps to save energy and reduce operating costs. This solution has significant potential for use in urban infrastructure, contributing to the improvement of the environment and quality of life.